Overcoming poisoning issues in hydrogen fuel cells with face-centered tetragonal FePt bimetallic catalysts - Choi, Daeil; Jang, Injoon; Lee, Taekyung; Kang, Yun Sik; Yoo, Sung Jong (Allerton Press Inc., 2025)
Hydrogen fuel cells are expected to play a central role in the next-generation energy paradigm. However, owing to practical limitations, hydrogen is supplied in the form of refined hydrocarbons or alcohols in industrial applications. Among them, methanol is widely used as a hydrogen source, and CO is inevitably generated during its oxidation process. Even a small amount of CO ( similar to 20 ppm) strongly binds to Pt used as a catalyst, and deactivates it. In addition to CO, surface adsorption of organic cations by binder or ionomer use in alkaline fuel cells is also one of the poisoning issues to be overcome. Herein, we propose FePt bimetallic catalysts that can resist unavoidable CO and organic cation poisoning. Our synthetic strategy, including annealing and acid treatment, allows the catalysts to possess different alloying degrees and surface structures, which in turn induce different levels of resistance to CO and organic-cation poisonings. The correlation between the surface and bulk structures of the catalysts and poisoning resistance was elucidated through X-ray photoemission spectroscopy and electrochemical analysis. The results revealed that an FePt catalyst having an ordered atomic arrangement displayed a better poisoning resistance than that having a disordered arrangement. (c) 2024 Published by Elsevier Ltd on behalf of The editorial office of Journal of Materials Science & Technology.